The effectiveness of solar radiation management using fine sea spray across multiple climatic regions - Z. Song; S. Yu; S. Yu; P. Li; N. Yao; N. Yao; L. Chen; L. Chen; Y. Sun; B. Jiang; D. Rosenfeld (Atmospheric Chemistry and Physics)
Marine cloud brightening (MCB) geoengineering aims to inject aerosols over oceans to brighten clouds and reflect more sunlight in order to offset the impacts of global warming or to achieve localized climate cooling. The relative contributions of direct and indirect effects in MCB implementations remain uncertain. Here, we quantify both effects by designing model simulations to simulate MCB for five open-ocean regions around the globe. Our results show that a uniform injection strategy that does not depend on wind speed captured the sensitive areas of the regions that produced the largest radiative perturbations during the implementation of MCB. When the injection amounts are low, the sea salt aerosol effect on shortwave radiation is dominated by the indirect effect via brightening clouds, showing obvious spatial heterogeneity. As the indirect effect of aerosols saturates with increasing injection rates, the direct effect increases linearly and exceeds the indirect effects, producing a consistent increase in the spatial distributions of top-of-atmosphere upward shortwave radiation. This study provides quantifiable radiation and cloud variability data for multiple regional MCB implementations and suggests that injection strategies can be optimized by adjusting injection amounts and selecting areas sensitive to injections.